PENANAMAN NILAI-NILAI KARAKTER PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI PONDOK PESANTREN PUTRI UMMI KALSUM DI LINGKUNGAN MASYARAKAT BERAGAMA - Fanny May Sarah; Syarbaini Saleh (STKIP Singkawang, 2024)
This research aims to examine: 1). How is the cultivation of character values of civic education learning at the ummi kalsum Islamic boarding school in the community 2) What is the role of civic education in shaping character in Islamic boarding schools 3) What are the contributions of Islamic boarding schools to the surrounding community in terms of civic values 4) How is the practice of instilling character values in ummi kalsum Islamic boarding schools in religious communities 5) What are the obstacles in instilling character values of civic learning. This research uses purposive sampling method, where the main informants are individuals who have in-depth understanding and direct involvement in the research context. The research subjects include Civic Education teachers, ustazahs of care, and santri wati. Data collection was conducted through observation, interviews, and documentation. Data analysis used a qualitative descriptive method, which involved the process of data reduction, data presentation, and conclusion drawing. The results showed that the cultivation of character values at the Ummi Kalsum Islamic Boarding School took place effectively both in the pesantren environment and the surrounding community. Citizenship Education plays an important role in shaping the character of religious, nationalist, and tolerant santri. Islamic boarding schools also make a significant contribution in strengthening civic values in society, especially in the context of religious diversity. However, this study found a number of obstacles, such as limited communication between the pesantren and parents and the varied attitudes of santri in accepting character values. Pesantren Putri Ummi Kalsum as the only pesantren in Nias Islands with a majority of non-Muslim communities, still strives to maintain and develop character education within the existing limitations.